QCD sum rule study on the fully strange tetraquark states of JPC = 2++ - Dong, Rui-Rui; Su, Niu; Chen, Hua-Xing; Cui, Er-Liang (Frontiers in Physics, 2023)
We apply the QCD sum rule method to systematically study the fully-strange tetraquark states with the quantum number J(PC)=2(++). We construct both the diquark-antidiquark and meson-meson currents, and calculate both their diagonal and off-diagonal correlation functions. Based on the obtained results, we further construct three mixing currents that are nearly non-correlated. We use one mixing current to extract the mass of the lowest-lying state to be 2.03+0.16-0.15 GeV, which can be used to explain the f2(2010) as a fully-strange tetraquark state of J(PC)=2(++). This state was observed by BESIII in the phi-phi channel, and we propose to confirm it in the eta(')-eta(') channel.